Self efficacy, Kepatuhan, HUBUNGAN SELF EFFICACY DENGAN TINGKAT KEPATUHAN PENGOBATAN HIPERTENSI DI PUSKESMAS BARENG KOTA MALANG - Ellia Ariesti (Jurnal Keperawatan Malang, 2018)
Abstract Hypertension is a risk factor for the occurrence of cardiovascular and cerebrovascular diseases. Identification of level of patient compliance in using drugs, especially in outpatients, needs to be done, given that patients use their own medication without supervision from health workers. In order to achieve effective treatment, nurses need to be involved in the program of delivering information about the treatment of hypertension through selfefficacy methods to support adherence in taking medication. The research method uses correlational research with a cross sectional research design that aims to see how the relationship between self-efficacy and the level of medication adherence in patients with hypertension in Bareng Health Center. The populations in this study were hypertensive patients who had been treated. The sample was determined using purposive sampling technique. The statistical test used Rank Spearmen Correlation test. The results of the study obtained significant values Sig. (2-tailed) is 0.155, where this result is >0.05, so it can be concluded that H0 failed to be rejected, namely there is no relationship between self-efficacy and adherence to elderly hypertension treatment. The absence of a relationship in this study was due to the fact that although most of the large outputs of respondents had moderate self-efficacy, the adherence to treatment was low, and also those who had high self-efficacy also had low treatment compliance; length of hypertension is still under 5 years and all respondents had no complications from hypertension even though most of them had received information from health workers, family support even had health insurance Keywords: Self efficacy, Compliance, Hypertension Treatment